The V30M Amyloidogenic Mutation Decreases the Rate of Refolding Kinetics of the Tetrameric Protein Transthyretin. Issue 5 (11th July 2012) - Jesus Jesus, Catarina S. H. Catarina S. H.; Vaz Vaz, Daniela C. Daniela C.; Saraiva Saraiva, Maria J. M. Maria J. M.; Brito Brito, Rui M. M. Rui M. M.
Abstract : Transthyretin (TTR) is a homotetrameric protein implicated in several amyloid diseases. The mechanism by which TTR is converted into elongated fibrillar assemblies has been extensively investigated, and numerous studies showed that dissociation of the native tetrameric structure into partially unfolded monomeric species precedes amyloid formation. The small differences observed in the crystal structures of different TTR variants, as well as the thermodynamics and kinetics of tetramer dissociation, do not seem to completely justify the amyloidogenic potential of different TTR variants. With this in mind, we have studied the refolding kinetics of WT-TTR and its most common amyloidogenic variant V30M-TTR, monitoring changes in intrinsic tryptophan fluorescence at different urea and protein concentrations. Our results demonstrate that the in vitro refolding mechanisms of WT- and V30M-TTR are similar, involving a dimeric intermediate. However, there are large differences in the refolding rate constants for the two variants, specially close to physiological conditions. Interestingly, tetramer formation occurs at a much slower rate in the amyloidogenic variant V30M-TTR than in WT-TTR, which in the in vivo setting may promote the accumulation of monomeric species in the extracellular environment, resulting in higher susceptibility for aggregation and amyloid formation instead of spontaneous refolding.